2016
DOI: 10.1590/1807-3107bor-2016.vol30.0041
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of clinical outcomes after periodontal treatment of aggressive periodontitis: 12-month randomized trial

Abstract: Little is known about the factors that may be used in clinical practice to predict the therapeutic response of aggressive periodontitis patients. The aim of this study was to determine predictors of clinical outcomes after non-surgical treatment of aggressive periodontitis. A total of 24 patients (aged 13-26 years) received oral hygiene instructions, as well as subgingival scaling and root planing. Twelve subjects received systemic azithromycin at random. Clinical variables were assessed at baseline, 3, 6, 9, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Despite the interesting clinical observation and risk assessment, this study included only clinical aspects in determining which variable represents a long‐term success predictor. Some other studies have also suggested the calprotectin levels in GCF, LPS response pattern and the presence of red complex pathogens in the subgingival biofilm as predictive factors of clinical response and future periodontal breakdown in GAgP patients . However, considering the complexity of the GAgP etiopathogenesis, evaluating the microbiological and immunological patterns in conjunction with clinical parameters is essential for risk assessment in that population.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Despite the interesting clinical observation and risk assessment, this study included only clinical aspects in determining which variable represents a long‐term success predictor. Some other studies have also suggested the calprotectin levels in GCF, LPS response pattern and the presence of red complex pathogens in the subgingival biofilm as predictive factors of clinical response and future periodontal breakdown in GAgP patients . However, considering the complexity of the GAgP etiopathogenesis, evaluating the microbiological and immunological patterns in conjunction with clinical parameters is essential for risk assessment in that population.…”
Section: Discussionmentioning
confidence: 99%
“…According to the authors, the inclusion of different parameters (such as probing depth ≥6 mm, bleeding index count ≥2, and different bone loss calculations) could be useful to modify the original PRA and better identify GAgP subjects with higher or lower‐risk for future tooth loss and periodontal destruction. Haas et al reported that patient and tooth factors could predict a better or worse response to treatment of localized and generalized aggressive periodontitis. Molars, absence of systemic antibiotic (azithromycin), localized aggressive periodontitis, infrabony defects and higher probing pocket depth resulted in a worse clinical response to non‐surgical therapy …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations